ANALISIS STABILITAS DINDING PENAHAN TANAH PADA LERENG SPILLWAY BENDUNGAN JLANTAH MENGGUNAKAN SOFTWERE PLAXIS - Abianto, Reki; Purnomoasri, RA Dinasty; Wibisono, Nur Muarif (Journal of Civil Engineering and Infrastructure Technology, 2025)
The Jlantah Dam is located in Jatiyoso District, Karanganyar Regency, Central Java. This dam construction has a total storage capacity of 10.97 million cubic meters, with a height of 70 meters from the riverbed, a length of 404 meters, a width of 12 meters, and a crest elevation of +690 meters. The purpose of this study is to examine the slope stability before reinforcing with retaining walls, the slope stability after reinforcement, and the sliding stability, overturning stability, and bearing capacity of the retaining walls. According to SNI 8640:2017, geotechnical design requirements define the slope safety factor. If the safety factor (SF) is more than 1.5, the slope is considered safe, whereas if the safety factor (SF) is less than 1.5, the slope is considered unsafe. The results of the slope stability analysis using PLAXIS 2D V20 software without retaining wall reinforcement show an SF = 1.253. The slope with reinforcement achieved an SF = 1.640. Using Geo5 2020 software with the Bishop method, the SF is 1.70, and with the Fellenius method, the SF is 3.36. For the retaining wall stability using the manual method, the sliding stability SF = 3.90, the overturning stability FS = 7.05, and the bearing capacity of the retaining wall FS = 12.25. Meanwhile, using Geo5 software, the sliding stability FS = 2.51, the overturning stability FS = 1.81, and the bearing capacity of the retaining wall FS = 3.36.